2018
DOI: 10.1063/1.5049204
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic-wave beam-scanning antenna using near-field rotatable graded-dielectric plates

Abstract: The paper proposes an electromagnetic-wave beam-scanning antenna system using a simple rotation of a pair of near-field graded-dielectric plates (GDPs). The antenna system requires an electromagnetic (EM) illuminator, with nearly symmetric aperture field distribution, as the base antenna and two types of GDPs: one radially graded dielectric (RGD) and two linearly graded dielectric (LGD) plates. The RGD first focuses the beam of the base antenna in the broadside direction, and the LGD then tilts the focused bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Unlike most of the above-mentioned techniques which have a by-product of slight gainreduction, metasurfaces can be utilized for mutual coupling reduction. Metasurfaces are 2D form of metamaterials and have exceptional abilities for controlling electromagnetic waves, which can be used for variety of applications, such as suppressing unwanted coupling effects, beamsteering [6,8]. In [6], a waveguide based metasurface was designed to exhibit a bandgap with two transmission zeros, which attributed to negative permeability and negative permittivity in the vicinity of magnetic resonance and electric resonance, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike most of the above-mentioned techniques which have a by-product of slight gainreduction, metasurfaces can be utilized for mutual coupling reduction. Metasurfaces are 2D form of metamaterials and have exceptional abilities for controlling electromagnetic waves, which can be used for variety of applications, such as suppressing unwanted coupling effects, beamsteering [6,8]. In [6], a waveguide based metasurface was designed to exhibit a bandgap with two transmission zeros, which attributed to negative permeability and negative permittivity in the vicinity of magnetic resonance and electric resonance, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Working as a spatial filter, traditional frequency selective surface (FSS) is constituted by an infinite array of metallic patterns printed on a dielectric substrate to control the transmission and reflection of an incident electromagnetic wave [1]. Additionally, it is reported that FSSs can be made of different materials, like all-dielectric materials [2], printed surfaces [3], or all metal structures [4]. Since natural materials do not possess the characteristic of frequency selectivity, FSS is also classified as the concept of metasurface by some scholars, which has gained a lot of attention over the past decade [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Frequency selective surfaces (FSSs) are basically two-dimensional arrays of patches on a dielectric slab or that of apertures within a metallic screen to perform the desired filtering operation [1]. There are some other FSSs made of only dielectrics [2][3][4] which are useful for large bandwidth, wideband near-field correction, and beam-scanning applications, respectively. Though the use of traditional LC filters fulfills the requirement of a filtering system in some cases, its use is not suitable at all situations.…”
Section: Introductionmentioning
confidence: 99%